2013
DOI: 10.1097/mou.0b013e32836320a7
|View full text |Cite
|
Sign up to set email alerts
|

The use of preoperative targeted molecular therapy to allow nephron sparing for T1b tumors

Abstract: In selected cases, TMT before NSS is well tolerated, effective and feasible. Still, this topic is considered experimental because it has not been thoroughly studied to fully assess the indications, the timing of therapy, and its effect on outcomes. Further evidence is needed to draw definitive conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, the surgical benefits after NT in mRCC have generally been observed during the immunotherapy era. While the use of preoperative TT in the setting of locally advanced or metastatic RCC (mRCC) remains in its preliminary stages, with only a few retrospective studies and case reports (2161718), there is a growing body of evidence that may support its role in a select group of patients (8). Therefore, the present study is significant because few studies have evaluated neoadjuvant TT in Asian populations (19), and, to the best of our knowledge, this is the first and only study of NT using a targeted agent in Korean patients with mRCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, the surgical benefits after NT in mRCC have generally been observed during the immunotherapy era. While the use of preoperative TT in the setting of locally advanced or metastatic RCC (mRCC) remains in its preliminary stages, with only a few retrospective studies and case reports (2161718), there is a growing body of evidence that may support its role in a select group of patients (8). Therefore, the present study is significant because few studies have evaluated neoadjuvant TT in Asian populations (19), and, to the best of our knowledge, this is the first and only study of NT using a targeted agent in Korean patients with mRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted therapy has shown efficacy in the downstaging of locally advanced tumours including those with caval thrombi in anecdotal reports [27]. Current evidence suggests that targeted therapy could be effective in downstaging tumours to allow NSS, especially in those with absolute indications [28,29]. A phase II trial of 25 patients using 8 weeks of neoadjuvant pazopanib in localized RCC (median tumour size 7.3 cm) showed that NSS was possible in 6 out of 13 patients in whom it was not possible at baseline [30].…”
Section: Downstaging Of Tumours With Targeted Therapymentioning
confidence: 99%
“…However, the tumor location and size may make these treatments difficult due to the potential adverse effects on adjacent organs, blood vessels, and the urinary tract. There have been several reports on the efficacy of preoperative molecular-targeted drugs for T1b tumors in nephron-sparing surgery [3,4]. However, only one case report regarding local ablative therapy is available in the literature [5].…”
Section: Introductionmentioning
confidence: 99%